Psychological Resilience and its Relationship with the Level of Life Quality Among the Education Preparation Diploma Students in faculty of Education of Tishreen University - Field study - Sbeira , Fouad; Ismael , Razan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to know the Psychological Resilience and the Life Quality Among the Education Preparation Diploma Students in faculty of Education of Tishreen University, And realized the relationship between Psychological Resilience and the Life Quality, also aimed to examine the differences in resilience and Life Quality according to the variables (six, specialty) the Students. The research used Descriptive analytical method, The sample included (272) students in the academic year 2016/2017. The research used Psychological Resilience and the Life Quality measures. The following statistical methods were used: means, t – test, and Pearson Correlation. Validity of the questionnaire was established though a jury of (7) of the teaching staff. Pilot sample consisted of (50) students. Reliability was established by Cronbach – Alpha Reliability at lest (0.88) for Life Quality measure, and (0.86) for Psychological Resilience measure. The final results showed that the Psychological Resilience and Life Quality were middle rated for the sample research. In fact, there are positivism relationship between Psychological Resilience and the Life Quality for the Students. There were no significant differences in resilience related to the specialty, and sex on the Life Quality measure. Also there were no significant differences in resilience related to the specialty, but there were significant differences related to the sex on the Psychological Resilience measure in favor of the male.